Información e interpretación en la cobertura periodística de los atentados del 11 de septiembre: la televisión y la prensa - Edo, Concha (Estudios sobre el Mensaje Periodístico, 2002)
One of the main characteristics in todays society of mass media is the power of the image in conveing with the minimum words the visual details of some news.Yet journalism of good quality pretends to offer even more. The still recent attacks on New York and Washington have shown once more that there are differences between the press and television, in the showing and in the interpretatin of the news. To know about the real causes of the events, the press has been the necessary complement reaffirming, with different shades in Europe and in the United States, the greater possibility of thinking over events of such magnitud.
Keywords: Journalism; Information; Interpretation; Interpretative Journalism; Trends in Journalism; Press; Television; Infographafic